Optix regulates nanomorphology of butterfly scales primarily via its effects on pigmentation - Banerjee, Tirtha Das; Finet, Cédric; Seah, Kwi Shan; Monteiro, Antónia (Frontiers in Ecology and Evolution, 2024)
Previous studies have shown that Optix regulates lower lamina thickness and the type of pigment that is produced in wing scales of a few butterfly species. However, the role of Optix in regulating pigment production across species, and in regulating additional aspects of scale morphology remains to be investigated. By combining microspectrophotometry, scanning electron microscopy, and focused ion beam technology on wild-type and Optix Bicyclus anynana crispants, we show that Optix regulates the production of orange pigments (ommochromes), represses the production of brown pigments (melanins), and regulates the morphology of the lower and upper surface of orange scales. Our findings suggest a conserved role of Optix as a switch gene that activates ommochrome and represses melanin synthesis across butterflies. By comparing these effects with other mutations, where only melanin is removed from scales, we propose that pigmentary changes, alone, affect the way that chitin polymerizes within a scale, changing lower lamina thickness as well as multiple intricate structures of the upper surface.